ICTMI 2017 Proceedings of the International Conference on Translational Medicine and Imaging - Gulyás, Balázs; Padmanabhan, Parasuraman; Fred, A. Lenin; Kumar, T. R. Santhosh; Kumar, Sundramurthy (Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the latest research presented at the International Conference on Translational Medicine and Imaging (ICTMI) 2017. This event brought together the world's leading scientists, engineers and clinicians from a wide range of disciplines in the field of medical imaging. Bioimaging has continued to evolve across a wide spectrum of applications from diagnostics and personalized therapy to the mechanistic understanding of biological processes, and as a result there is ever-increasing demand for more robust methods and their integration with clinical and molecular data. This book presents a number of these methods.